Selection and Application of the Data Transfer Operating Protocol Software Architecture for the Software-Defined Radio - Oleg V. Vorobyov; Alexey I. Rybakov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Noise-proof coding is used in many communication systems to provide an acceptable level of performance. A particular feature of its use is the inclusion of redundant characters in a coded packet. It demands more transfer time and essentially better throughput of the channel than in the case of an uncoded packet transferring. A promising development is a software change in the configuration of radio communication system and the development of communication protocols. This is done to ensure the maximum load factor of the channel while ensuring an acceptable level of performance. Objective. To improve radio system performance by updating communication protocols, in order to solve the problem of ensuring maximum channel load during signal formation and reception. Materials and methods. The paper describes the structure of the protocol developed by the authors. It is applicable in software to control ionospheric radio communication system transceiver modules. The software was developed in LabView (VHDL language) cross-platform software environment and was studied by means of a radio interface simulation model. Results. The study examined the corrective ability of codes in the case of a supplementary Gaussian channel with binary phase modulation (OFDM-modulation, 2PSK and 4PSK absolute phase manipulation) in the selection of an energy-efficient approach to the design of ionospheric radio communication system. The study developed the structure and the functional description of the protocol used in the software for the simulation model of software-configurable radio channel. The software operation can be carried out in Windows 7 and in later versions with bit depth x32/x64 under the MS VisualC++package. It was shown that the software thus developed can use the hardware and software controls of the transceiver module. SunSDR2 transceiver and antenna amplifier were included in the module. Conclusion. The results obtained allow for the replacement of separately adjusted radio receivers and transceivers built on a complex super-heterodyne scheme. A limited number of hardware units operate under the control of the developed software. Further studies will be carried out to assess the passage of OFDM signals through multipath communication channels with Rician and Rayleigh fadings. The resulting model will allow for the assessment of noise immunity at different lengths of the cyclic prefix OFDM symbol and for observation of signal constellation behaviour under the influence of various instabilities.